Kubhist 2: Carlscronas Wekoblad 1830's - Språkbanken Text (University of Gothenburg, 2024)
Part of the collection Kubhist 2

Del av samlingen Kubhist 2
Kubhist 2: Carlscronas Wekoblad 1830-talet
Keywords: Language Technology (Computational Linguistics); corpus; Natural Language Processing; Språkbehandling och datorlingvistik